Development of the System of Education Management in the Republic of Kazakhstan - Želvys, Rimantas; Aganina, Kundyz; Zhunusbekova, Aziza (Pedagogika, 2014)
The article discusses the possibilities of developing the system of education management in Kazakhstan. The long-term strategy “Kazakhstan-2050” indicates that education is one of the main priorities for the Kazakh state. The main goal of education reforms in Kazakhstan is to adapt the system of education to a changing socio-economic environment of the country. Professional specialists in the field of education management are vitally important as they will have to reform and manage the newly developing system of education. Many national and foreign researchers assume that the most effective way of training education managers is granting them a higher education degree. In order to find out what is the opinion of students studying in the field of education, a preliminary survey of students at a National Abai Pedagogical University was conducted. 140 students of pedagogical-psychological studies on a Masters level were interviewed, including 90 women and 50 men. 79 percent of respondents acknowledged the importance of studying education management. 86 percent claim that education management should be studied on a Masters level, 7 percent prefer to study education management on a Bachelor, and 7 percent – on a Doctoral level. Preliminary survey showed that majority of respondents prefer to study education management on a Masters level; however, currently there are no Masters studies of education management in Kazakhstan, as well as in other Central Asian republics – Kyrgyzstan and Tajikistan. Studies of education management are limited to specialized courses in pedagogical high schools and in-service teachers training institutes. The Tempus EDUCA project “Modernization and development of teacher training and education management studies in Central Asia” is supposed to help in dealing with this problem. The aim of the project is to introduce competence-based learning and management training in the systems of higher education in three Central Asian countries. The education management program developed by the authors of the article is aimed at Masters students and teachers of primary education at National Abai Pedagogical University; however, the program should also contribute to further development of education management in Kazakhstan.